A novel approach to assessing the antioxidant and anti-diabetic potential of synthesized calcium carbonate nanoparticles using various extracts of Ailanthus altissima - Samad, Noreen; Ejaz, Umer; Kousar, Saba; Al-Mutairi, Aamal A.; Khalid, Arslan; Amin, Zeemal Seemab; Bashir, Shahzad; Al-Hussain, Sami A.; Irfan, Ali; Zaki, Magdi E. A. (Frontiers in Chemistry, 2024)
Calcium carbonate nanoparticles (CaCO3) have been found to exhibit unique properties that show their potential to be used in various therapies. Green synthesis of CaCO3 has been progressively gaining ac-ceptance due to its cost-effectiveness and energy-efficient nature. In the current study, different extracts of Ailanthus altissima were used to synthesize the calcium carbonate nanoparticles the synthesis and characterization of CCNPs were confirmed by using Fourier Transform Infra-Red spectroscopy, UV-Vis spectroscopy, and Scanning Electron Microscopy (SEM). The antioxidant activities (hydrogen peroxide, phosphomolydbenum, and ferric reducing) of calcium carbonate nanoparticles were affirmed by a good range of percentages of inhibition against free radical scavenging. The antidebate assays of CCNPs were observed by in-vitro and in silico approaches in a range at various concentrations while maximum inhibition occurred. In conclusion, the current study depicted that conjugated CaCO3 with A. altissima has a good potential to cure oxidative stress and Type II diabetes and could be used in the future as biogenic nanomedicine for the treatment of other metabolic diseases.